Speaking of God in Stand Your Ground Times - Douglas, Kelly Brown (Lumen et Vita, 2016)
Dr. Kelly Brown Douglas is Professor of Religion at Goucher College where she holds the Susan D. Morgan Professorship of Religion. She is widely published in national and international journals and other publications. As a leading voice in the development of a womanist theology, Essence magazine counts Douglas “among this country’s most distinguished religious thinkers, teachers, ministers, and counselors.” Her groundbreaking and widely used book Sexuality and the Black Church: A Womanist Perspective (1999) was the first to address the issue of homophobia within the black church community. Dr. Douglas has been a pioneering and highly sought after voice in regard to addressing sexual issues in relation to the black religious community. She has been very active in advocating equal rights for LGBT persons. Her latest book, Stand Your Ground: Black Bodies and the Justice of God (2015) examines the challenges of a “Stand Your Ground” culture for the Black Church and all black bodies. Other books include The Black Christ (1994), What’s Faith Got to Do With It?:Black Bodies/Christian Souls (2005),and Black Bodies and the Black Church: A Blues Slant (2012). Dr. Douglas is also the co-editor of Sexuality and the Sacred: Sources for Theological Reflection (2010). Douglas is a Phi Beta Kappa graduate of Denison where she earned a bachelor of science summa cum laude in psychology. She went on to earn a master of divinity and a doctoral degree in systematic theology from Union Theological Seminary (New York City). Rev. Douglas was ordained at Ohio’s St. Margaret's Episcopal Church in 1985. She received the Anna Julia Cooper Award by the Union of Black Episcopalians (July 2012) for “her literary boldness and leadership in the development of a womanist theology and discussing the complexities of Christian faith in African-American contexts.” Rev. Douglas was an Associate Priest at Holy Comforter Episcopal Church in Washington, D.C. for over 20 years. She currently serves at the Washington National Cathedral.